Production chain of commercial alginate from sargassum (Macrocystis Pyrifera) in Peru - Chavez Jimenez, Mario Sebastian (2024)
Peru is a privileged country regarding marine hydrobiological resources due to the vast variety of algae and the biomass they possess. This advantage allows Peru to develop an industrial sector to produce hydrocolloids, a group of natural polymers, chemically known as polysaccharides, derived from marine algae. Among the most widely used hydrocolloids is commercial alginate, an input used in different industries such as food, cosmetics, chemicals, and textiles. This study aimed to identify and characterize the strategic variables that integrate the commercial alginate production chain from sargassum (Macrocystis pyrifera) in Peru and the social stakeholders that lead it. Based on an exploratory and descriptive scope, a structural analysis was conducted (using the theoretical bases of French Strategic Foresight as a methodological design) with the support of a panel of seven experts knowledgeable about the system studied and the MICMAC tool (Matrix of Cross Impacts and a Multiplication Applied to a Classification). The outcome shows that the key variables of the production chain are competitive prices, sales levels, potential markets, and quality control. Simultaneously, identifying the most influential social stakeholders made it possible to propose strategies to control the variables to shape and control the chain adequately. This study lays the foundations for the strategic planning of future scenarios for the system in the long term.